Determining the Effects of Environmental Events on Cultured Atlantic Salmon Behaviour Using 3-Dimensional Acoustic Telemetry - Stockwell, Caitlin L.; Filgueira, Ramón; Grant, Jon (Frontiers in Animal Science, 2021)
The health and welfare of farmed fish are highly dependent on environmental conditions. Under suboptimal conditions, the negative impact on welfare can cause changes in fish behavior. Acoustic tags can provide high resolution and high frequency data to monitor fish positioning within the cage, which can be used to infer swimming behavior. In this study, implanted acoustic tags were used to monitor the three-dimensional positioning of Atlantic salmon (Salmo salar) at a commercial farm in Nova Scotia, Canada. The one-month study period allowed the characterization of background behavior and changes in behavior in relation to different environmental conditions, namely, water characteristics in terms of dissolved oxygen and temperature caused by the fall overturn, storm conditions, and feeding activity. The three-dimensional position of 15 fish was recorded using high temporal resolution (3 s). Fish movement was characterized by calculating four fish variables: distance from the center of the cage [m], depth [m], velocity [ms-1], and turning angle [°]. The population swam in a counterclockwise swimming direction around 4 ± 2 m depth at an average speed of 0.61 ± 0.38 ms-1. After the fall overturn, the population moved significantly towards cage center while decreasing velocity, and non-significant differences in depth and turning angle were observed. During feeding periods, a significant increase in depth and velocity, as well as a reduction in turning angle were observed. The storm event did not cause any significant change in the four fish variables. While some of the behavioral changes were difficult to assess with respect to causation, the high resolution, high frequency data provide unique detailed positioning information to further our understanding of the swimming behavior of farmed fish.